Probable Serotonin Syndrome Precipitated by the Addition of Trazodone to Lurasidone and Valproic Acid: A Case Report - Do, André; Kachichian, Raffi; Vincent, Philippe (Santé mentale au Québec, 2026)
Serotonin syndrome (SS) is a serious medical condition characterized by altered mental status, autonomic instability and neuromuscular abnormalities. It is caused by the use of one or multiple serotoninergic medication(s), which results in excessive activation of serotoninergic receptors. Here, we present a case of probable SS following the addition of trazodone to treat insomnia. Besides trazodone, the patient was prescribed valproic acid, lurasidone, estradiol, dexlansoprazole and spironolactone. A few hours after taking trazodone 100 mg, the patient developed several physical symptoms, including chills, nausea, sweating, dizziness, generalized muscle stiffness and tremor. The symptoms were associated with significant functional impairment and gradually subsided over the next 48 hours. No physical examination or laboratory test were performed when the patient was symptomatic. However, the patient meets the diagnostic criteria for SS using the Sternbach criteria. Although most cases of SS associated with trazodone involve selective serotonin reuptake inhibitor antidepressants, this case report suggests that the combination of trazodone, lurasidone and valproic acid can lead to excessive serotoninergic activity via serotonin reuptake inhibition, 5-HT1A partial agonism and increased central serotoninergic neurotransmission. Therefore, clinicians should exercise caution when trazodone is combined with a second-generation antipsychotic and valproic acid.